Re-classification of Rhipidiomorphus malaccanus Pic, a long-neglected genus and species of Psephenoidinae (Coleoptera: Psephenidae) - Jeng, Ming-Luen (Zootaxa, 2012)
In his long career, Maurice Pic (1866–1957), a prolific French entomologist, described many thousands of insect species, subspecies, and varieties, as well as several hundreds, if not more than a thousand, of new genera across orders and families (Villiers 1958a, b). The majority of Pic’s described taxa are beetles, especially in Tenebrionoidea and the former Malacodermata (or Malacodermatidae). Many genera were described in a brief and uninformative style and without explicit family assignment, making it difficult to determine their familial affiliation based on the literature (Pollock 2005). Accordingly, several taxa have remained little known or long-neglected until now. Most of Pic’s type material is deposited in the Muséum national d'Histoire naturelle, Paris (MNHN), where it is possible to examine and provide a possibility to reliably determine their identities.